The F130S point mutation in the Arabidopsis high-affinity K+ transporter AtHAK5 increases K+ over Na+ and Cs+ selectivity and confers Na+ and Cs+ tolerance to yeast under heterologous expression - Alemán, Fernando; Caballero, Fernando; Ródenas, Reyes; Rivero, Rosa M.; Martínez, Vicente; Rubio, Francisco (Frontiers in Plant Science, 2014)
Potassium (K+) is an essential macronutrient required for plant growth, development and high yield production of crops. Members of group I of the KT/HAK/KUP family of transporters, such as HAK5, are key components for K+ acquisition by plant roots at low external K+ concentrations. Certain abiotic stress conditions such as salinity or Cs+-polluted soils may jeopardize plant K+ nutrition because HAK5-mediated K+ transport is inhibited by Na+ and Cs+. Here, by screening in yeast a randomly-mutated collection of AtHAK5 transporters, a new mutation in AtHAK5 sequence is identified that greatly increases Na+ tolerance. The single point mutation F130S, affecting an amino acid residue conserved in HAK5 transporters from several species, confers high salt tolerance, as well as Cs+ tolerance. This mutation increases more than 100-fold the affinity of AtHAK5 for K+ and reduces the Ki values for Na+ and Cs+, suggesting that the F130 residue may contribute to the structure of the pore region involved in K+ binding. In addition, this mutation increases the Vmax for K+. All this changes occur without increasing the amount of the AtHAK5 protein in yeast and support the idea that this residue is contributing to shape the selectivity filter of the AtHAK5 transporter.